2014
DOI: 10.7150/ijms.8025
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset Depression in the Absence of Stroke: Associated with Silent Brain Infarctions, Microbleeds and Lesion Locations

Abstract: Background: Late-onset depression (LOD) is a frequent mood disorder among elderly. Previous studies have proved that LOD is associated with cerebral silent lesions especially white matter lesions (WML) and yielded the “vascular depression” hypothesis to explain the pathogenesis of LOD. However, there were relatively few studies about the association between silent brain infarctions (SBIs), microbleeds (MBs) and the prevalence of LOD. In this study we sought to evaluate the presence, accumulation and locations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 30 publications
2
27
2
Order By: Relevance
“…Indeed, other studies with similar sample sizes and using both conventional neuroimaging sequences and DTI found results similar to ours (Lamar et al ., ). Considering other SVD lesions, one study found an association between microbleeds and depressive symptoms (Wu et al ., ). A recent meta‐analysis including 12 studies showed that lacunar stroke patients had a non‐significant higher prevalence of depression compared with patients with non‐lacunar cerebrovascular diseases (Egeto et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, other studies with similar sample sizes and using both conventional neuroimaging sequences and DTI found results similar to ours (Lamar et al ., ). Considering other SVD lesions, one study found an association between microbleeds and depressive symptoms (Wu et al ., ). A recent meta‐analysis including 12 studies showed that lacunar stroke patients had a non‐significant higher prevalence of depression compared with patients with non‐lacunar cerebrovascular diseases (Egeto et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…LLD can be further divided into early-onset depression (EOD) (onset before 60e65 years) and late-onset depression (LOD) (Mackin et al, 2014;Sachs-Ericsson et al, 2012;Wu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This is evidence of cerebral infarction on imaging without acute neurological dysfunction attributable to the lesion 11 , and is commonly investigated using MRI. Studies 12,13 have shown that silent cerebral infarction is associated with an increased risk of future stroke, dementia, depression, cognitive impairment and early death independent of other vascular risk factors. It is well recognized following other catheter-based procedures (cerebral 14,15 and coronary 16 angiography, carotid stenting 17 and transcatheter aortic valve implantation 18 ), and a recent study 19 of 19 patients reported an incidence of 63 per cent following TEVAR.…”
Section: Introductionmentioning
confidence: 99%